2021
DOI: 10.3390/ijms22158289
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the Molecular Clock: The Importance of Circadian Rhythms in the Development of Glioblastomas and Its Intervention as a Therapeutic Strategy

Abstract: Gliomas are solid tumors of the central nervous system (CNS) that originated from different glial cells. The World Health Organization (WHO) classifies these tumors into four groups (I–IV) with increasing malignancy. Glioblastoma (GBM) is the most common and aggressive type of brain tumor classified as grade IV. GBMs are resistant to conventional therapies with poor prognosis after diagnosis even when the Stupp protocol that combines surgery and radiochemotherapy is applied. Nowadays, few novel therapeutic str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 245 publications
(343 reference statements)
0
9
0
Order By: Relevance
“…Based on the results described above together with the recently reported data, 89 future targeting of BMAL1 , CLOCK or genes from the PER family may represent promising therapeutic targets for treatment of glioblastoma.…”
Section: Elements Of Clock As Therapeutic Targetsmentioning
confidence: 71%
“…Based on the results described above together with the recently reported data, 89 future targeting of BMAL1 , CLOCK or genes from the PER family may represent promising therapeutic targets for treatment of glioblastoma.…”
Section: Elements Of Clock As Therapeutic Targetsmentioning
confidence: 71%
“…GBM is a highly vascularized and invasive brain tumor with a poor prognosis. Median patient survival after diagnosis is 12-15 months and there are no full curative therapies (reviewed in [42]). Recent evidence in the field shows that circadian clock function should be considered a novel target to design new therapeutic strategies or improve the current approaches to treat high-grade gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the World Health Organization (WHO) classification, GBMs are grade 4 brain tumors resistant to conventional therapies; they represent 45.2% of all malignant central nervous system (CNS) tumors and 80% of all primary malignant CNS tumors [23]. The standard of care treatment is the Stupp protocol, which combines radiotherapy followed by the administration of the DNA-alkylating chemotherapeutic temozolomide (TMZ) (reviewed in [24]). Though the TMZ regimen was approved by the US Food and Drug Administration (FDA), its chemotherapeutic efficiency is poor and most patients relapse [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the study of alterations in circadian rhythm genes has emerged in different types of cancer, including GB [20]. Previous reports suggested that circadian rhythm genes play essential roles in different aspects of tumor progression.…”
Section: Introductionmentioning
confidence: 99%